Jet-induced inertial instabilities and the growth of mesoscale convective systems - Blanchard, David O., author (Colorado State University. Libraries, 1995)
Many mesoscale convective systems (MCSs) have been observed to form in environments where the isentropic absolute vorticity may have values that approach zero, resulting in regions with weak inertial stability. It has been demonstrated that for a given amount of convective available potential energy (CAPE), deep convective circulations can be modified and enhanced as the inertial stability is reduced. Consequently, there has been speculation that the evolution and organization of convection into MCSs may be related to the presence of an environment in which the inertial stability is weak or unstable. In some mesoscale environments, particularly in the springtime when CAPE is large and a strong jet stream is still present, the atmosphere is unstable to both upright and slantwise convection. Because the time scales of these two modes are considerably different, upright convection will typically dominate. It is hypothesized that this upright convection can, over longer time scales, exploit the weak restoring force present in the mesoscale inertial stability. To explore the hypothesis that inertial instability plays a role in the development of mesoscale growth and organization, both observational and model data were examined. Environments that supported the growth of MCSs in the PRE-STORM network were sampled with high quality special soundings. Secondary circulations that occurred in the presence of inertial instabilies were analyzed and documented using the high spatial and temporal resolution rawinsonde data from the PRE-STORM field program. Additional examples of MCS environments were examined using data from the MAPS analysis system. The high resolution of the model, coupled with the ingest of multiple data types, result in the improved analysis of small-scale and short-lived features such as mesoscale inertial instabilities. To increase the understanding of the basic processes that enhance MCS growth in inertially unstable environments, the RAMS mesoscale model was used. Model results indicate that the strength of the divergent outflow was strongly linked to the degree of inertial stability in the local environment. The results also showed a strong dependence on the magnitude of the Coriolis parameter. Finally, simulations using varying degrees of vertical stability indicated that there was also significant sensitivity to this parameter.
January 5, 1995.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1994.
Keywords: Convection (Meteorology); Atmospheric circulation